BRINGING EA INTO ELT’S CLASSROOM: Rising Students’ Awareness to Avoid Errors - Budianto Hamuddin (ELT-Lectura, 2015)
This paper presents the importance of Error Analysis (EA) in English language teaching (ELT) classroom, bygiving a systematic review of the concepts and theories concerning Error Analysis, as well as the various reasons causing errors are comprehensively explored. This article aims to introduce and give a brief picture of the causes and types from grammatical errors to the students in ELT classroom start from collecting samples of learner language, identifying the errors in the sample, describing these errors, classifying them according to their nature and causes, and evaluating the students seriousness. The idea of Error Analysis brought into ELT classroom, promising an advantageous and benefits for both learners and lectures. The activity Involves For learners, error analysis uses to show and introduce the types of errors, so they will know how to avoid of having the errors in their sentences Whereas for lecturers it is required to evaluate themselves whether they are successful or not in teaching English.